AT2 and MAS (but not AT1) angiotensinergic receptors in the medial amygdaloid nucleus modulate the baroreflex activity in rats - Costa-Ferreira, Willian [UNESP]; Gomes-de-Souza, Lucas [UNESP]; Crestani, Carlos C. [UNESP] (Springer Nature, 2019)
The medial amygdaloid nucleus (MeA) is a limbic structure that has been demonstrated to be part of the central circuitry regulating baroreflex function. However, the local neurochemical mechanisms involved in baroreflex control by this forebrain structure is poorly understood. Thus, in the present study, we investigated the specific role of AT1, AT2, and MAS angiotensinergic receptors within the MeA in baroreflex responses in unanesthetized rats. For this, the baroreflex function was assessed using both the pharmacological approach via intravenous infusion of vasoactive agents and the sequence analysis technique. Using the pharmacological approach, we observed that bilateral microinjection of the selective AT2 receptor antagonist PD123319 into the MeA increased the tachycardia evoked by blood pressure decrease, but without affecting the reflex bradycardia caused by blood pressure increase. Besides, bilateral microinjection of the selective MAS receptor antagonist A-779 decreased both tachycardic and bradycardic responses of the baroreflex. The sequence analysis technique indicated that PD123319 into the MeA increased baroreflex effectiveness index while A-779 had an opposite effect. Treatment of the MeA with the selective AT1 receptor antagonist losartan did not affect baroreflex function assessed by either the pharmacological approach or sequence analysis technique. Overall, these findings provide evidence that MAS receptor within the MeA plays a facilitatory role in baroreflex function, whereas local AT2 receptor inhibits cardiac baroreflex responses. Results also indicate that AT1 receptor within the MeA is not involved in the control of baroreflex function.
Keywords: A-779; Amygdala; AT2 receptor; Blood pressure; Heart rate; Losartan; MAS receptor; PD123319